Reframing blackness and black solidarities through anti-colonial and decolonial prisms - Dei, George J. Sefa (George Jerry Sefa), 1954- (Critical studies of education, 2017)
This book grounds particular struggles at the curious interface of skin, body, psyche, hegemonies and politics. Specifically, it adds to current [re]theorizations of Blackness, anti-Blackness and Black solidarities, through anti-colonial and decolonial prisms. The discussion challenges the reductionism of contemporary polity of Blackness in regards to capitalism/globalization, particularly when relegated to the colonial power and privileged experiences of settler. The book does so by arguing that this practice perpetuates procedures of violence and social injustice upon Black and African peoples. The book brings critical readings to Black racial identity, representation and politics informed by pertinent questions: What are the tools/frameworks Black peoples in Euro-American/Canadian contexts can deploy to forge community and solidarity, and to resist anti-Black racism and other social oppressions? What critical analytical tools can be developed to account for Black lived experiences, agency and resistance? What are the limits of the tools or frameworks for anti-racist, anti-colonial work? How do such critical tools or frameworks of Blackness and anti-Blackness assist in anti-racist and anti-colonial practice? The book provides new coordinates for collective and global mobilization by troubling the politics of "decolonizing solidarity" as pointing to new ways for forging critical friends and political workers. The book concludes by offering some important lessons for teaching and learning about Blackness and anti-Blackness confronting some contemporary issues of schooling and education in Euro-American contexts, and suggesting ways to foster dialogic and generative forums for such critical discussions